Design, fabrication and characterization of circular ZnO TFT for UV detection applications. (January 2023) - Alharbi, Abdullah G.; Shafi, Nawaz
Abstract: Here-in this work, we for the first time report a circular zinc oxide (ZnO) based thin film transistor (TFT) and experimentally demonstrate its applicability as ultraviolet (UV-365 nm) photo-detector. The circular TFT has been fabricated through RF-magnetron sputtering process. Prior to fabrication the design is simulated in Atlas TCAD. The morphological, and optical properties of fabricated TFT were analyzed through scanning electron microscope (SEM), atomic force microscope (AFM), x-ray diffraction and UV-spectrometer and ellipsometry. The dark condition measurements revealed saturation current of 1 μ A, considerable carrier mobility of 0.08 cm 2 V -1 s -1 and ON-state to OFF-state drain current ratio of 1 0 5 . Illuminating the device by UV light leads to substantial increment in ON-state as well as OFF-state current reducing to current ratio to 1 0 4 . It is observed that for wavelength of 290 nm and applied bias of 10V, the responsivity was measured to be about 4.17 A/W yielding a rejection ratio of 7 . 28 × 1 0 5 . The employment of circular structural design for TFT can open up new dimensions and possibilities to improve the performance in photo-detection applications. This indicates that the fabricated circular TFT was highly sensitive towards UV wavelengths and can be a potential candidate for solar blind applications. Highlights: First of its kind: A circular TFT structure. Simulation, fabrication and UV detection characterization of circular ZnO thin film transistor. Measurements of photo-responsivity and transient response of the fabricated device for ultra-violet wavelength.